Understanding user attitude towards ai agents: the roles of perceived competence, trust in technology, and social influence - Bo, Duan; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study investigates the impact of perceived competence, trust in technology, and social influence on user attitude towards AI agents. Utilizing a quantitative research design, a sample of 434 participants was surveyed to analyze the relationships between these factors and their influence on attitude towards AI. Pearson correlation and multiple regression analyses were conducted to evaluate the data. The results revealed that perceived competence was the strongest predictor of positive user attitude towards AI agents, followed by trust in technology and social influence. These findings highlight the critical importance of ensuring that AI systems are perceived as competent and trustworthy to foster positive user attitudes. Additionally, social influence plays a significant role in shaping how users perceive AI, indicating that peer opinions and social networks impact user attitudes. The study underscores the need for developers and policymakers to focus on enhancing AI competence, building trust through transparency, and leveraging social influence to promote positive user interactions with AI technologies. Recommendations for practical applications include improving AI system functionalities, implementing robust data privacy measures, and engaging in targeted social marketing strategies.